2022
DOI: 10.1128/jcm.01597-21
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Diagnostic Accuracy of Eight Commercial Assays for the Detection of Rubella Virus-Specific IgM Antibodies

Abstract: Rubella and congenital rubella syndrome are caused by the rubella virus and are preventable through vaccination, making disease eradication possible. Monitoring of progress towards global eradication and local elimination requires high quality, sensitive disease surveillance that includes laboratory confirmation of cases. Previous evaluations of anti-rubella IgM detection methods resulted in the broad adoption of Enzygnost (most recently manufactured by Siemens) enzyme-linked immunosorbent assay (ELISA or EIA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Confirmation of clinical symptoms and history of exposure to measles using a laboratory-based anti-measles immunoglobulin M (IgM) ELISA is the standard method of diagnosis. Several commercial assays of varying accuracy exist to detect anti-measles IgM, including those against virus lysate and nucleoprotein ( 11 ). To determine whether we could detect anti-measles dIgA, we employed a modified indirect ELISA protocol using Euroimmun kits as well as in-house measles virus lysate-coated plates for the detection of antigen-specific dIgA in the plasma of individuals with acute measles infection and other viral exanthema conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Confirmation of clinical symptoms and history of exposure to measles using a laboratory-based anti-measles immunoglobulin M (IgM) ELISA is the standard method of diagnosis. Several commercial assays of varying accuracy exist to detect anti-measles IgM, including those against virus lysate and nucleoprotein ( 11 ). To determine whether we could detect anti-measles dIgA, we employed a modified indirect ELISA protocol using Euroimmun kits as well as in-house measles virus lysate-coated plates for the detection of antigen-specific dIgA in the plasma of individuals with acute measles infection and other viral exanthema conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Assays were repeated in a validation panel comprising anonymized residual sera referred to the National Microbiology Lab (Winnipeg, Canada) for serological testing and included sera from laboratory-confirmed measles cases ( n = 50), sera with provisional diagnosis of rubella ( n = 36), roseola ( n = 40), chikungunya/dengue/zika ( n = 41), parvovirus ( n = 35), and other fever and rash illness of unknown etiology ( n = 37). This complete panel was previously used to evaluate the diagnostic accuracy of commercial assays for the detection of measles-specific IgM antibodies ( 11 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heibert and colleagues recently evaluated the test characteristics of eight commercially available measles IgM kits, including the kits from Virion/Serion, Euroimmun, and IBL that are included in our current study (11). This report found that IgM capture assays had the best sensitivity and specificity for detecting measles IgM antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies ( 12 16 ) in our analysis contained data for the discontinued Siemens Enzygnost kits. For reader’s interest, we have included these forest plots in the supplementary data showing how the Siemens Enzygnost kits performed compared to the other index tests (Fig.…”
Section: Methodsmentioning
confidence: 99%